2008
DOI: 10.1016/j.jbiomech.2007.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Flexor tendon and synovial gliding during simultaneous and single digit flexion in idiopathic carpal tunnel syndrome

Abstract: The characteristic pathological finding in carpal tunnel syndrome (CTS) is non-inflammatory fibrosis of the subsynovial connective tissue (SSCT), which lies between the flexor tendons and the visceral synovium (VS). How this fibrosis might affect tendon function is unknown. To better understand the normal function of the SSCT, the relative motion of the middle finger flexor digitorum superficialis (FDS III) tendon and VS was observed during finger flexion in patients with CTS and cadavers with a history of CTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 22 publications
7
43
1
Order By: Relevance
“…12,14 Our findings are also consistent with other studies of the SSCT in humans, which have shown that the SSCT from CTS patients had higher shear modulus and shear strength than normal SSCT, and that SSCT from CTS patients had decreased gliding characteristics compared to normal SSCT. 37,38 Gels seeded with patients’ SSCT fibroblasts had a higher contraction rate, tensile strength and stiffness than those seeded with normal control cells, as demonstrated by Yang et al 18 In addition, the decay time constant, tensile strength and Young’s modulus were all significantly strengthened by treatment with exogenous TGF-β1 in all cell types in this study. This finding is also compatible with our previous studies, which examined the effects of TGF-β1 using collagen gel contraction models with canine and human cells.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…12,14 Our findings are also consistent with other studies of the SSCT in humans, which have shown that the SSCT from CTS patients had higher shear modulus and shear strength than normal SSCT, and that SSCT from CTS patients had decreased gliding characteristics compared to normal SSCT. 37,38 Gels seeded with patients’ SSCT fibroblasts had a higher contraction rate, tensile strength and stiffness than those seeded with normal control cells, as demonstrated by Yang et al 18 In addition, the decay time constant, tensile strength and Young’s modulus were all significantly strengthened by treatment with exogenous TGF-β1 in all cell types in this study. This finding is also compatible with our previous studies, which examined the effects of TGF-β1 using collagen gel contraction models with canine and human cells.…”
Section: Discussionsupporting
confidence: 71%
“…These results are consistent with the results in other cell-seeded gel contraction models. 12,14,18,37,38 …”
Section: Discussionmentioning
confidence: 99%
“…The subsynovial connective tissue (SSCT), which fills the space between the tendons, and the space between the tendons and the median nerve, is normally filmy and supple, and thus could facilitates the smooth gliding of the median nerve between the flexor tendons and flexor retinaculum during finger and wrist movements. In patients with CTS, the SSCT becomes fibrotic and stiff, which could alter the gliding characteristics of the SSCT, and, thus of the nerve as well (Ettema, Amadio 2004, Ettema, An 2008, Ettema, Zhao 2007, Lluch 1992, Oh, Zhao 2006). We hypothesize that nerve and tendon motion patterns that are altered by SSCT fibrosis might be useful to identify CTS prodromes, and perhaps even as ‘biomarkers’ that might suggest treatments to restore or preserve nerve mobility before symptoms become so severe that surgery is needed, and we plan to investigate this possibility in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Changes to the subsynovial connective tissue (SSCT) suggest that shear forces from differential tendon motion are involved in injury development (Ettema et al, 2006). Fibrosis of the SSCT influences tendon gliding in the carpal tunnel, resulting in adherence or dissociation between the flexor tendons and the tenosynovium (Ettema et al, 2008), and might decrease range of motion. Flexor tendon gliding changes may increase frictional forces even further, resulting in a vicious cycle of degradation (Ettema et al, 2008;2006), and have been shown to increase when one finger is moved alone compared to moving all fingers in unison .…”
Section: Introductionmentioning
confidence: 99%